2014
DOI: 10.1128/mcb.01651-13
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Rb and E2f8 Synergizes To Trigger Stressed DNA Replication during Erythroid Terminal Differentiation

Abstract: f Rb is critical for promoting cell cycle exit in cells undergoing terminal differentiation. Here we show that during erythroid terminal differentiation, Rb plays a previously unappreciated and unorthodox role in promoting DNA replication and cell cycle progression. Specifically, inactivation of Rb in erythroid cells led to stressed DNA replication, increased DNA damage, and impaired cell cycle progression, culminating in defective terminal differentiation and anemia. Importantly, all of these defects associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…It has been shown that inactivation of both Rb and E2F8 works synergistically to trigger DNA replication. 50 In addition, E2F8 is essential for polyploidization in mammalian cells. 51 The detailed information for the role of E2F family in cancer has been described in a recent review.…”
Section: P16/rb/e2f Pathway In Liver Proliferation After Ph and In LImentioning
confidence: 99%
“…It has been shown that inactivation of both Rb and E2F8 works synergistically to trigger DNA replication. 50 In addition, E2F8 is essential for polyploidization in mammalian cells. 51 The detailed information for the role of E2F family in cancer has been described in a recent review.…”
Section: P16/rb/e2f Pathway In Liver Proliferation After Ph and In LImentioning
confidence: 99%
“…Previously, gene expression studies have demonstrated that, of all E2F transcription factor genes, E2f2 is most significantly induced in terminally differentiating cells of the definitive erythroid lineage (in bone marrow and fetal liver) (7,21). In agreement with these gene expression data, we found that E2F-2 protein is significantly upregulated in primary bone marrow erythroid cells, sorted based on CD44/Ter119/forward scatter (FSC) (22) to distinguish basophilic erythroblasts (RII), polychromatic erythroblasts (RIII), and orthochromatic erythroblasts (RIV) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Erythroblasts exit the mitotic cell cycle before undergoing enucleation; this exit occurs concomitantly with the induction of cyclindependent kinase (Cdk) inhibitors, including p21 Cip1 and p27 Kip1 (2)(3)(4). Loss of retinoblastoma (Rb), the master regulator of G 1 -to-S-phase progression, results in ineffective erythropoiesis in vivo (5)(6)(7)(8). Upstream mitogen-stimulated pathway signaling converges upon the G 1 cyclin-Cdks, leading to Rb hyperphosphorylation and E2F transcription factor activation (9-11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although E2F8 has previously been shown to promote erythroid terminal differentiation by collaborating with Rb protein where Rb binds and sequesters E2F2 and E2F8 competes with E2F2 for E2F2-binding sites on target gene promoters (Ghazaryan, Sy et al 2014), to our knowledge, there is no reported data showing the participation of E2F8 in the differentiation program in KCs. Dysregulation of squamous differentiation is a key event in malignant conversion of KCs and is evident in early forms of SCC (Sugiyama, Speight et al 1993;Watanabe, Ichikawa et al 1995;Gasparoni, Fonzi et al 2004).…”
Section: Atypical E2f Proteins and Differentiationmentioning
confidence: 81%